ANALISIS KINERJA LALU LINTAS RUAS JALAN DI KABUPATEN SUMBAWA MENGGUNAKAN PTV VISSIM (STUDY OF ROAD TRAFFIC MANAGEMENT AND ENGINEERING IN SUMBAWA DISTRICT) - FERA FITRI SALSABILA; DESI WIDIANTY; RATNA YUNIARTI; KHAIRUNISA APRILIANA; I DEWA MADE ALIT KARYAWAN; ACHMAD FAJAR NAROTAMA SARJAN (Universitas Mahasaraswati K. Mataram, 2024)
To anticipate the potential trends of traffic problems in the future, a series of traffic management and engineering efforts need to be carried out on the roads in Sumbawa Regency (Sumbawa Besar). This study aims to obtain a traffic study of the road segments in Sumbawa Regency to implement traffic management and engineering. The study was conducted on six road segments using inventory surveys and Traffic Counting (TC), as well as 21 intersections using inventory surveys and Classified Turning Moving Counting (CTMC), which were then analyzed using the PTV Vissim application. Based on the analysis, the results indicate that the signal cycle change scenario can improve the level of service at signalized intersections. In addition, a comparison was made between alternatives and existing conditions in traffic safety management, which resulted in better existing conditions.